(3GdZQGeI GdJgOjOjI cLRGA dYOe JfajP CMcGe GdbVGA GdEOGQj GdUGOQI VO GdEOGQI (B/s - (3CMeO, efUhQ eMeOs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2002)
(3GdEWGQ GdYGe ddZQGeI GdJgOjOjI,eaghe GdZQGeI GdJgOjOjI,JejjR GdZQGeI GdJgOjOjI Yf ZjQgG ef GdCSGdjH GdbQjHI efgG,eQMdI YOe GdGYJQGa GdJTQjYj HGdZQGeI GdJgOjOjI,GdGYJQGa GdJTQjYj HGdZQGeI GdJgOjOjI,fWGb JWHjb GdZQGeI GdJgOjOjI ef MjK GdeMd(B-(3eUOQ GdMce(B-(3ef MjK eOi SdWI GdbVGA GdEOGQj HTCf GdfRGY eMd GdMce(B-(3ef MjK eOi EecGfjI GdWYf aj GdMce(B-(3ef MjK GdCTNGU GdPjf JWHb Ydjge,LgI GdbVGA GdEOGQj GdeNJUI HJhbjY GdZQGeI GdJgOjOjI,GdMGdGJ GdJj jecf ajgG QaV JhbjY GdZQGeI GdJgOjOjI,JShjI GdZQGeI GdJgOjOjIs
(3HHdjhZQGajG(B:(3U(B.211-224s
Keywords: (3GdbVGA GdEOGQjs